Evaluating sorghum cultivars for grain and straw yield - McIntire, John M.; Reed, J.D.; Jutzi, S.C.; Tedla, A.; Kebede, Y. (International Livestock Centre for Africa, 1988)
Proposes a method to estimate the trade-off between sorghum grain and straw yield in agronomic trials. Describes a theory of the conflict between the two products. presents data from sorghum cultivar trials in Ethiopia, as well as a method of evaluating sorghum grain and straw.